2014
DOI: 10.1111/ped.12428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle weakness distribution on balance in neuromuscular disease

Abstract: The distal group was particularly affected regarding dynamic balance, and the proximal group regarding static balance. Muscle strength was important for providing dynamic stability in the distal group, and for maintaining proximal stabilization during dynamic activities in the proximal group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The association between muscle weakness and standing impairments is reported by several authors19202627, and, in the current study, it is supported by the following two outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The association between muscle weakness and standing impairments is reported by several authors19202627, and, in the current study, it is supported by the following two outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The present study aimed to identify and interpret stabilometric variables that assess the static postural control of children and adolescents with CMT and shows ways of using CoP to maintain postural stability, in the presence of distal weakness and somatosensory impairments. Studies in the literature have shown that stabilometric assessment is capable of distinguishing poor and appropriate balance in children[ 9 , 49 52 ] and adults[ 23 25 , 53 , 54 ]. To the extent of our knowledge, this is the first original study focused on classical stabilometric parameters, in children and adolescents with CMT.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent of our knowledge, this is the first original study focused on classical stabilometric parameters, in children and adolescents with CMT. Kaya et al [ 52 ]explored only the percentage of oscillation of CoP in children with Duchenne muscular dystrophy and different polyneuropathic diseases, while others have studied balance impairment in adults with neuropathies[ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakness in the upper and lower limbs is a common symptom of multiple diseases, including neuromuscular disorders ( 14 ), amyotrophic lateral sclerosis ( 15 ), multiple sclerosis, Guillain-Barre syndrome, transverse myelitis ( 16 ), hypovitaminosis D ( 17 ) and POEMS syndrome. Hence, presentation with weakness in the upper and lower limbs in patients with POEMS syndrome may not result in the correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%